Viral proteins expressed on the surface of murine leukemia cells. - Ledbetter, J (1977)
Leukemic cells of AKR mice contain as constituents of their membranes the murine leukemia virus envelope protein gp70 and the precursor polyprotein of the viral internal (core) structural proteins. Both gp70 and the core polyprotein are represented on the cell surface as glycoproteins, as evidenced by incorporation of [3H]glucosamine into their structure and the binding of these proteins to lectins. The glycosylated core polyprotein exists in at least two serologically distinguishable forms: the 95,000-dalton polyprotein reacts with antisera prepared against the viral proteins p30, p12, and p10, whereas the 85,000-dalton polyprotein reacts with antisera prepared against the viral proteins p30 and p12, but not p10. Additional heterogeneity in these cell surface polyproteins has been observed wtih leukemias induced by exogenous leukemia viruses. Spontaneous leukemia cells of AKR mice invariably express gp70 and the core polyprotein on their cell surface; normal thymocytes of young AKR mice express gp70, but not the core polyprotein on their surface.